2010
DOI: 10.1007/s11999-010-1318-4
|View full text |Cite
|
Sign up to set email alerts
|

Do Men Outperform Women During Orthopaedic Residency Training?

Abstract: Background Orthopaedic surgery residency has one of the lowest percentages of women (13.1%) of all primary surgical specialties. There are many possible reasons for this, including bias during the selection process. Questions/purposes We therefore asked whether performance during residency might adversely bias the selection of future female orthopaedic residents by researching whether males and females perform equally in orthopaedic surgery residency. Methods Ninety-seven residents enrolled in our residency be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
24
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 46 publications
(27 citation statements)
references
References 11 publications
2
24
0
1
Order By: Relevance
“…The fact that women choose orthopaedics for occupation-related and intellectual reasons correlates well with the finding in a study of 90 residents that women and men in residency performed similarly by objective and subjective measures [15]. Women reported higher satisfaction with career choice than their male colleagues [18]. Although increased attrition rates of women orthopaedic surgery residents have been described in the past [23], a recent study does not substantiate this finding [18].…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…The fact that women choose orthopaedics for occupation-related and intellectual reasons correlates well with the finding in a study of 90 residents that women and men in residency performed similarly by objective and subjective measures [15]. Women reported higher satisfaction with career choice than their male colleagues [18]. Although increased attrition rates of women orthopaedic surgery residents have been described in the past [23], a recent study does not substantiate this finding [18].…”
Section: Discussionsupporting
confidence: 55%
“…Women reported higher satisfaction with career choice than their male colleagues [18]. Although increased attrition rates of women orthopaedic surgery residents have been described in the past [23], a recent study does not substantiate this finding [18]. Additionally, concerted efforts to increase diversity through targeted programming and recruitment have been described [21].…”
Section: Discussionmentioning
confidence: 99%
“…In terms of absolute numbers, the most popular specialty is sports (94 females) followed by pediatrics (79), hip and knee/tumor (45), foot and ankle (42), trauma (38), shoulder (22), and spine (15).…”
Section: Resultsmentioning
confidence: 99%
“…In a paper on whether men outperform women during orthopaedic residency training, it was found for 90 residents in a program, there was no difference between male and female performance, and therefore performance, during residency should not bias any future selection for residency [15]. This also seems to be applicable for applying for fellowships.…”
Section: Discussionmentioning
confidence: 97%
“…We distributed a survey that focused on exposure to orthopedic surgery to all members of the Ruth Jackson Orthopaedic Society. Of the 777 members, 267 (34%) female orthopedic surgeons and residents responded ( Table 2) Previous research has shown that women's performance in orthopedic residency programs equals that of men, 8 and that women are accepted into orthopedic surgery residency programs at the same rate as men. 9 However, women are more underrepresented in orthopedics than in any other specialty.…”
mentioning
confidence: 99%